Adult-onset still’s disease: a case report and a comprehensive review - Mathews, Aswathy; Prazad, Amal; Neville, Brandon (International Journal of Research in Medical Sciences, 2024)
Adult-onset still disease (AOSD) is a rare inflammatory disorder affecting young adults, especially women, characterized by fever, arthralgia, skin rash, hyperleukocytosis and increased ferritin levels. It can be monocyclic, polycyclic, or chronic, with chronic cases primarily involving the joints. Ferritin, a protein that stores iron in the body, can be significantly elevated in AOSD due to systemic inflammation and the body’s response to it. Treatment typically includes corticosteroids, methotrexate, and biological therapy. Recent treatments like anakinra, tocilizumab, and TNFα-blockers have shown promise. This case report details a 26-year-old woman with a one-month history of fever, arthralgia, and weight loss. She was diagnosed with a new onset AOSD, based on elevated ferritin, liver enzymes, IL-6, and IL-18 levels. Her symptoms improved with systemic corticosteroid therapy, and she was discharged with oral steroids, NSAIDS and regular follow-ups.